Comparing political regimes : a thematic introduction to comparative politics - Siaroff, Alan (Book collections on Project MUSE., 2013)
"Comparing Political Regimes provides a comprehensive assessment of the world?s political systems by outlining and contrasting the aspects of four different regime types: liberal democracies, electoral democracies, semi-liberal autocracies, and closed autocracies."